(untitled) (Південний архів (історичні науки), 2023)
The research purpose is to find evidence for dating one of the elements of the defense complex of the Akkerman fortress – glacis. The methodological basis of the research was the analysis of historiography, as well as cartographic, iconographic and archaeological sources, the method of comparative typological analysis in the field of defense architecture. The main results of the research. In historiography, different opinions have been expressed more than once regarding the dating of the glacis of the fortress. All of them fluctuated within the middle of the 15th cent. – to early 1790s. The reason for such wide spread in dates was the lack of a clear understanding of the defensive functions of the glacis, the lack of a convincing and universal building-periodization of the fortress (especially for later periods), insufficient knowledge of the source base on the history of Akkerman of the Turkish period. The fortress was built in the 15th century on the right bank of the Dniester estuary and throughout its history remained without fundamental changes in its plan and constructive features. Only in 1795–1796 Turkish authorities are starting to implement the most ambitious project to modernize it. Its goal was to bring the complex into line with defense standards in the face of advanced gunpowder firearms. In 1792, Akkerman became a border point due to the delimitation of the borders with the Russian Empire along the banks of the Dniester estuary. As a result of the modernization, carried out according to the project of the French engineer F. Kauffer, a series of internal and external additional earthworks is being erected, one of which was a glacis on the esplanade, in the perimeter of the outer edge of the moat. Conclusions. The key to the dating was in the design plan for the reconstruction of the fortress by F. Kauffer, which dates back to the second half of 1793. At the same time, a series of written and epigraphic sources make it possible to confidently date the implementation of this project three years later. The mistakes of the predecessors in dating this element of defense consisted in the perception of the glacis as a derivative of the moat in a clear connection with it. Also, archaeological excavations of ancient Tyra in the 1900s-1960s, carried out “on the glacis”, confused the understanding of its chronology due to carelessness in the use of fortification terms and vague concepts.